Discovery of High X-Ray Polarization from the Neutron Star Low-mass X-Ray Binary Cyg X-2 on the Horizontal Branch - Gnarini, Andrea; Ravi, Swati; Kaaret, Philip; Bobrikova, Anna; Poutanen, Juri; Forsblom, Sofia V.; Ursini, Francesco; Baglio, Maria Cristina; Bianchi, Stefano; Capitanio, Fiamma; Cocchi, Massimo; Teodori; et al. (Institute of Physics Publishing, 2026)
We present results from simultaneous X-ray polarimetric and spectroscopic observations of the bright neutron star low-mass X-ray binary Cyg X-2, performed by the Imaging X-ray Polarimetry Explorer (IXPE) and the Nuclear Spectroscopic Telescope Array. IXPE detected significant polarization (15σ) from the source in the 2–8 keV energy band with an average polarization degree (PD) of 4.5% ± 0.3% and a polarization angle (PA) of 128° ± 2° as the source moved along the horizontal branch of its Z-track. The PD increases with energy reaching 9.9% ± 2.8% in the 7–8 keV band, with no evidence for energy-dependent variation in the PA. The PA is roughly consistent with previous measurements obtained during the normal and flaring branches and also with the known radio jet axis. From spectropolarimetric analysis, the main contribution to the polarized radiation is due to Comptonized photons, but the polarization is higher than predicted in typical spreading layer geometries. The observed high polarization may be due to a combination of a highly polarized reflected component and a moderately polarized spreading layer on the neutron star surface or produced by electron scattering in an equatorial wind.